Estimating Carbon Stocks and Sequestration With Their Valuation Under a Changing Land Use Scenario: A Multi-Temporal Research in Abha City, Saudi Arabia - Mallick, Javed; Almesfer, Mohammed K.; Alsubih, Majed; Ahmed, Mohd; Ben Kahla, Nabil (Frontiers in Ecology and Evolution, 2022)
Urbanization and land-use change are significant contributors to cumulative greenhouse gas emissions, causing climate change and environmental damage. Research on land-use-derived carbon storage and sequestration capability is crucial for emission reduction strategy and sustainable development. Because cities are becoming significant sources of carbon emissions, an accurate assessment of city-level carbon storage and sequestration is now required. This study intended to estimate the carbon storage and sequestration capabilities using the InVEST model under different land use land cover (LULC) classes in Abha, Saudi Arabia. We used a support vector machine (SVM) for LULC mapping. For the future forecasting of the LULC map, we employed cellular automata (ANN-CA). Expansion of built-up land is the primary source of CO2. From 1990 to 2040, agriculture lost 145 Megagram of carbon per hectare (Mg C/ha), whereas vegetation lost 34948.15 Mg C/ha. Vegetation would get 17363.7 Mg C/ha during the same period, whereas urban areas would receive 3924.1 Mg C/ha. Approximately 17000 Mg C/ha would be lost from the vegetation area in future periods. The approaches outlined in this paper may add a new dimension to carbon emission analyses and provide helpful information for low-carbon city